TJOKROAMINOTO'S INTEGRATION OF ISLAMIC PRINCIPLES AND SOCIALIST IDEALS : A HISTORICAL ANALYSIS - Farida Novita Rahmah; Lailatul Dzikriyah; Fadlilah Novia Rahmah (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
This article aims to discuss Tjokroamninoto's thoughts on the discourse of Islam and socialism. The method used is the Historical method, which includes four stages, namely, heuristic, criticism, interpretation, and historiography. The main source used is Tjokroaminoto's own book, entitled